Management of receivables on the example of business entities from the P±ock Subregion - Barbara Felic; Magdalena Grabowska; Agnieszka Krzętowska; Marlena Piekut; Renata Walczak (Foundations of Management, 2013)
The article presents a problem and differences of financial liquidity and profitability. The survey of financial liquidity and profitability, underwritten by the College of Economics and Social Sciences of Warsaw University of Technology, was conducted on P±ock Subregion enterprises. The survey concerned cash flow management, receivables controlling, trade credits, different payments and receivables. The results of the conducted survey indicate that the majority of companies from the subregion of P±ock suffer several problems and despite a wide range of possibilities of using different tools for the management of receivables, the respondents do not use them efficiently. The survey has shown that most of them applies only the most popular, simplest and cheapest solutions, but, consequently the least efficient.
Keywords: 650; financial liquidity; profitability; subregion of P±ock